Diffusion-weighted imaging (DWI) ischemic volume is related to FLAIR hyperintensity-DWI mismatch and functional outcome after endovascular therapy - Jiang, Liang; Peng, Mingyang; Chen, Huiyou; Geng, Wen; Zhao, Boxiang; Yin, Xindao; Chen, Yu-Chen; Su, Haobo (Quantitative Imaging in Medicine and Surgery; Vol 10, No 2 (February 21, 2020): Quantitative Imaging in Medicine and Surgery, 2020)
Background: We assessed whether diffusion-weighted imaging (DWI) volume was associated with fluid- attenuated inversion recovery vascular hyperintensities (FVH)-DWI mismatch and functional outcome in patients with acute stroke who received endovascular therapy (EVT). Methods: Fifty-three acute stroke patients who received EVT were enrolled. FVH-DWI mismatch, DWI volume on admission, DWI volume on follow-up, DWI volume growth, the functional outcome at 3 months (mRS) and other clinical data were collected. Receiver operating characteristic (ROC) analysis was performed to evaluate the value of DWI volume in predicting functional outcome after stroke. Results: The FVH-DWI mismatch group had a smaller DWI volume on admission (13.86±19.58 vs. 65.07±52.21; t=−4.301, P=0.000), a smaller DWI volume on follow-up (29.88±33.52 vs. 112.43±87.19; t=−4.143, P=0.000), and a lower DWI volume growth (16.02±19.90 vs. 47.36±40.06; t=−3.326, P=0.003) than those of the no FVH-DWI mismatch group. The good functional outcome group had a smaller DWI volume on admission (13.30±13.26 vs. 68.56±54.28; t=−5.611, P=0.000), a smaller DWI volume on follow-up (27.65±18.80 vs. 120.25±90.37; t=−5.720, P=0.000), lower DWI volume growth (14.35±15.06 vs. 51.69±41.17; t=−4.737, P=0.001) and a higher FVH-DWI mismatch ratio (75.76% vs. 35%; t=8.647; P=0.004) than those of the poor functional outcome group. ROC analysis showed that the sensitivity and specificity of DWI volume on admission for predicting functional outcome were 65% and 96.97%, respectively (the optimal cut-off value: 33.50 mL); DWI volume on follow-up was 48.6 mL, with a sensitivity and specificity of 80% and 87.88%, respectively; DWI volume growth was 22.25 mL, with a sensitivity and specificity of 70% and 87.88%, respectively. Conclusions: DWI volume and DWI volume growth can provide the prognostic information of acute stroke patients after thrombectomy.